Stochastic neuron based on IGZO Schottky diodes for neuromorphic computing - Dang, Bingjie; Liu, Keqin; Zhu, Jiadi; Xu, Liying; Zhang, Teng; Cheng, Caidie; Wang, Hong; Yang, Yuchao; Hao, Yue; Huang, Ru (APL materials, 2019)
Neuromorphic architectures based on memristive neurons and synapses hold great prospect in achieving highly intelligent and efficient computing systems. Here, we show that a Schottky diode based on Cu-Ta/InGaZnO4 (IGZO)/TiN structure can exhibit threshold switching behavior after electroforming and in turn be used to implement an artificial neuron with inherently stochastic dynamics. The threshold switching originates from the Cu filament formation and spontaneous Cu–In–O precipitation in IGZO. The nucleation and precipitation of Cu–In–O phase are stochastic in nature, which leads to the stochasticity of the artificial neuron. It is demonstrated that IGZO based stochastic neurons can be used for global minimum computation with random walk algorithm, making it promising for robust neuromorphic computation.